Emergence of Naegleria fowleri as a fatal parasite in Pakistan - Ahmed, Sharmeen; Shazia Rahim; Muhammad Faraz; Syed Muhammad Hassan (Journal of the Pakistan Medical Association, 2024)
Madam, Naegleria fowleri, a life-threatening flagellate, causes a fulminating disease called Primary Amoebic Meningoencephalitis (PAM) which rapidly becomes fatal. The symptoms of PAM include headache, vomiting, stiff neck, seizures, and cerebral haemorrhages, eventually leading to death within 48 hours after the onset. The discovery of the first case of Naegleriasis in the US has led to considerable attention to research towards it. Since then, 39 other countries have fallen prey to the brain-eating parasite with Pakistan being the 2nd most affected country after the Southern US (1). Statistically, Pakistan recorded 105 deaths from PAM exclusively from 2008-2017 with the highest yearly toll of 22 registered deaths solely in 2012 (2). The aforementioned concerning facts raise a noteworthy inquiry: Why is N. fowleri becoming increasingly fatal in Pakistan? Substandard primary prevention and misdiagnosis of PAM appear to be the primary factors at play. In Pakistan, inadequate chlorination of swimming pools, storage of water in overhead tanks exceeding the temperature of 44°C and improper sanitation of drinking water are primary factors fuelling the spread of the thermophilic parasite. The mounting rise in global warming, severe heat waves and newfound resistance to drugs are the latest contributing factors to the escalating mortality rates due to N. fowleri. It is, however, noteworthy that the leading predisposing cause of PAM in Pakistan is ablution with tap water while a history of swimming/diving is essentially absent in most clinical scenarios. Amphotericin B and Miltefosine show positive results against PAM, however, further research is needed to conclude their effectivity (3). Vaccines play a vital role in therapeutic interventions and can help prevent the spread of N. fowleri (4). However, due to lack of resources and funding, Pakistan has failed to be on the front lines in the development of the vaccine. The misdiagnosis of PAM can be considered as yet another pillar of inadequate secondary prevention (5). It is due to the close resemblance of the clinical picture with Acute Bacterial Meningitis (ABM) which is far more widespread and requires an entirely different approach towards management. Secondly, a prevalent occurrence among patients is to inadvertently or intentionally omit vital information while providing medical history which leads to oversight of details like recent recreational water activities (6). The short incubation period of the disease also highlights the importance of prompt diagnosis. —Continue